2015
DOI: 10.1371/journal.pone.0127396
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness in Dementia with Lewy Bodies and Alzheimer's Disease: A Comparison of Prodromal and Dementia Stages

Abstract: ObjectivesTo assess and compare cortical thickness (CTh) of patients with prodromal Dementia with Lewy bodies (pro-DLB), prodromal Alzheimer's disease (pro-AD), DLB dementia (DLB-d), AD dementia (AD-d) and normal ageing.MethodsStudy participants(28 pro-DLB, 27 pro-AD, 31 DLB-d, 54 AD-d and 33 elderly controls) underwent 3Tesla T1 3D MRI and detailed clinical and cognitive assessments. We used FreeSurfer analysis package to measure CTh and investigate patterns of cortical thinning across groups.ResultsCompariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
85
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 42 publications
17
85
1
6
Order By: Relevance
“…7) stages, in accordance with previous reports (Blanc et al, 2015, Lerch, 2004). Other regions, including the temporal, parietal and frontal lobes (Dickerson et al, 2009) showed cortical thickness reduction only at moderate and advanced stages of AD (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…7) stages, in accordance with previous reports (Blanc et al, 2015, Lerch, 2004). Other regions, including the temporal, parietal and frontal lobes (Dickerson et al, 2009) showed cortical thickness reduction only at moderate and advanced stages of AD (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…It may be that higher glucose levels lead to grey matter atrophy via cerebral glucose hypometabolism, which leads to neuronal injury, which has been shown to be independent of Aβ accumulation [48]. Although research has shown that cortical thinning occurs in the prodromal stages of several types of dementia (i.e., dementia with Lewy bodies, AD, and vascular dementia) [4,13,14, 35], few studies have investigated cortical thickness in a cognitively normal, healthy sample [17,34,42]. …”
Section: Discussionmentioning
confidence: 99%
“…In this sense, several recent studies have analyzed and compared the local thickness between healthy controls and patients suffering MCI and AD [Blanc et al, 2015;Delli Pizzi et al, 2014;Julkunen et al, 2009;Li et al, 2011;Mak et al, 2015;Wang et al, 2016;Zhao et al, 2015] (in Wang et al, 2016, LGI is also analyzed). In general, they reported significant differences between HC and AD in similar regions as our findings, including the bilateral temporal cortex, and distributed regions in the parietal and frontal lobe [Blanc et al, 2015;Delli Pizzi et al, 2014;Li et al, 2011;Zhao et al, 2015]. The study presented in Mak et al [2015] is a longitudinal analysis involving the percent change of thickness over 12 months (longitudinal cortical thinning).…”
Section: Figurementioning
confidence: 99%